PENGARUH EDUKASI GIZI METODE SCAVENGER HUNT TERHADAP TINGKAT PENGETAHUAN DAN SIKAP ANEMIA PADA REMAJA PUTRI DI SMP ATTAQWA-03 BEKASI - Ahmad, Maghdalena Ardilah; Hakiem Afrizal, Sandra (Lafadz Jaya Publisher, 2024)
Anemia is a nutritional problem that affects more for women rather than men. Anemia can be caused by several factors, one of which is lack of knowledge and attitude towards anemia. Several interventions may prevent anemia such as to increase the intake of nutrients through nutritional education which may increase knowledge and attitudes to prevent anemia. The purpose of this study was to determine the differences in the level of knowledge and attitude toward anemia in adolescent girls after providing nutrition education using the scavenger hunt method at Attaqwa-03 Junior High School, Bekasi. This type of research is pre-experimental with a pretest-posttest one group design. The respondents in this study were 56 female students. Data analysis with univariate analysis and bivariate analysis using paired samples t-test with statistical significance p <0.05. The results of univariate analysis showed that the respondents with upper level of knowledge before intervention was 3,6% and after intervention was 71,4%. While the level of good attitude amongst respondents before intervention was 87,5% and after intervention was 100%. The results of bivariate analysis showed that there were significant changes before and after the intervention with a change in the average knowledge was p value 0.000. As well as on attitude is with a p value of 0.044. As conclusions, the scavenger hunt method is effectively improving knowledge and attitude towards anemia for female high school students.